Investigating Deep Eutectic Solvents (DESS) for Carbon Capture in the Oil and Gas Sector Through Process Simulation - Supardi, Nur Syazwani; Mat Isa, Norasikin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Rising carbon dioxide (CO2) emissions, especially from oil and gas operations, have sparked a critical need for better carbon capture methods in today's industrial landscape. Traditional monoethanolamine (MEA) systems, despite their widespread use, face mounting environmental concerns that point to the necessity of greener alternatives. This study investigates Deep Eutectic Solvents (DESs), with a focus on Reline - a unique blend of choline chloride and urea - as a potentially sustainable alternative. Industrial-scale simulations using DWSIM software indicated Reline's better CO2 absorption capabilities, which result from its optimized solubility and flow properties as compared to standard MEA systems. Environmental impact analysis using OpenLCA revealed that employing DESs resulted in dramatically decreased ecological consequences, notably in terms of toxicity and total environmental footprint. The findings establish DESs as a practical, scalable approach to industrial carbon capture that is consistent with global climate commitments under the Paris Agreement, while also closing the gap between theoretical DES applications and the practical demands of emission reduction in energy-intensive industries.